2021
DOI: 10.5507/ag.2021.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using the additional field player on attack efficiency during 2017 Women's Handball World Championship

Abstract: Background: Rule changes such as the use of the additional field player in the attack to replace the goalkeeper can significantly change the tactical strategies of the handball game. Objective: The aim of this study was to analyze the effectiveness of the use of the additional field player in offensive situations during the positional attack and counterattack suffered by the teams participating in the 2017 Women's Handball World Championship. Methods: The sample consisted of 15 matches in the knockout stage. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Existing data imply that the efficiency of using the empty-goal tactic depends crucially on timing, ability, and the score [ 18 ]. Some studies failed to detect a clear advantage (e.g., [ 16 ]); other suggested that playing with an additional field player during the critical periods of handball matches could change the momentum of the game [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing data imply that the efficiency of using the empty-goal tactic depends crucially on timing, ability, and the score [ 18 ]. Some studies failed to detect a clear advantage (e.g., [ 16 ]); other suggested that playing with an additional field player during the critical periods of handball matches could change the momentum of the game [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Krahenbühl et al [ 16 ] analyzed 15 games in the 2017 Women’s Handball World Championship and confirmed that the empty-goal rule is used mainly to offset the numerical imbalance caused by a two-minute suspension. They also reported that there was a significant increase in the number of errors when using the additional field player to gain numerical superiority in attack.…”
Section: Introductionmentioning
confidence: 99%